2012
DOI: 10.1136/postgradmedj-2011-130443
|View full text |Cite
|
Sign up to set email alerts
|

Xanthelasma palpebrarum: a marker of premature atherosclerosis (risk of atherosclerosis in xanthelasma)

Abstract: Alteration in apolipoprotein levels (A1 and B) in XP patients may predispose to cutaneous and systemic deposition of lipids, including atherosclerosis. Therefore, XP patients irrespective of their lesion size or serum lipid levels should be screened using CIMT for detection of subclinical atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 30 publications
3
41
3
2
Order By: Relevance
“…In a Danish prospective study (The Copenhagen City Heart Study) comprising almost 13 000 subjects followed up for more than 20 years, the presence of xanthelasma was associated with a significantly increased risk of myocardial infarction (by 48%), ischemic heart disease (by 38%), and ischemic disease of the lower extremities (by 70%), even after adjustment for some covariates, such as age, sex, diabetes mellitus, smoking, hypolipidemic treatment, and postmenopausal status 31 . Another study confirmed a significant association of xanthelasma with the prevalence of non-alcoholic fatty liver disease, recently assumed to be independent risk factor for ischemic heart disease 38 and with increased intima-media thickness 39 . Tendinous and tuberous xanthomas can signalise familial hypercholesterolemia and consequently the cardiovascular risk associated with elevated plasma concentrations of LDL cholesterol.…”
Section: Prognostic Significance Of Xanthomasmentioning
confidence: 50%
“…In a Danish prospective study (The Copenhagen City Heart Study) comprising almost 13 000 subjects followed up for more than 20 years, the presence of xanthelasma was associated with a significantly increased risk of myocardial infarction (by 48%), ischemic heart disease (by 38%), and ischemic disease of the lower extremities (by 70%), even after adjustment for some covariates, such as age, sex, diabetes mellitus, smoking, hypolipidemic treatment, and postmenopausal status 31 . Another study confirmed a significant association of xanthelasma with the prevalence of non-alcoholic fatty liver disease, recently assumed to be independent risk factor for ischemic heart disease 38 and with increased intima-media thickness 39 . Tendinous and tuberous xanthomas can signalise familial hypercholesterolemia and consequently the cardiovascular risk associated with elevated plasma concentrations of LDL cholesterol.…”
Section: Prognostic Significance Of Xanthomasmentioning
confidence: 50%
“…19 Unlike most studies, however, the mean LDL (120.3±43.6 mg/dl) level in our patients was not statistically different compared to the mean LDL (110.6± 26.7 mg/dl) level inthecontrol group. 3,8,11,20-22 …”
Section: Discussionmentioning
confidence: 99%
“…In another series, 7% of patients with xanthelasma had coronary artery disease [21]. Xanthelasma has been studied as a marker of premature atherosclerosis by discovering ultrasonographic thickening of the carotid intima [22]. Defects in lipoproteins, apolipoproteins (proteins that bind lipids and transport them through the lymphatic and circulatory systems), apoenzymes, and vascular permeability in the face of normal serum lipid levels are other possible contributing mechanisms for the genesis of xanthelasma [23-25].…”
Section: Discussionmentioning
confidence: 99%